2022
DOI: 10.3390/children9010118
|View full text |Cite
|
Sign up to set email alerts
|

New Insights from Metabolomics in Pediatric Renal Diseases

Abstract: Renal diseases in childhood form a spectrum of different conditions with potential long-term consequences. Given that, a great effort has been made by researchers to identify candidate biomarkers that are able to influence diagnosis and prognosis, in particular by using omics techniques (e.g., metabolomics, lipidomics, genomics, and transcriptomics). Over the past decades, metabolomics has added a promising number of ‘new’ biomarkers to the ‘old’ group through better physiopathological knowledge, paving the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 90 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Consistent with our finding, it has been reported that N6-carbamoylthreonyladenosine was significantly associated with systolic blood pressure ( 41 ). It has been identified as a biomarker for chronic kidney disease progression in children ( 50 , 51 ) and highly correlated with glomerular filtration rate ( 52 ). Hypertension can often lead to end organ damage including renal dysfunction and chronic kidney disease ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our finding, it has been reported that N6-carbamoylthreonyladenosine was significantly associated with systolic blood pressure ( 41 ). It has been identified as a biomarker for chronic kidney disease progression in children ( 50 , 51 ) and highly correlated with glomerular filtration rate ( 52 ). Hypertension can often lead to end organ damage including renal dysfunction and chronic kidney disease ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites, such as amino acids, sugars, and lipids, are intermediate or end products of cellular metabolism. Metabolomic analysis of biological fluids (e.g., blood and urine) has shown promise as a method for novel biomarker discovery in kidney disease [[15], [16]]. Two main analytical platforms used are magnetic resonance spectroscopy and mass spectrometry, usually coupled with modern separation techniques (such as liquid/gas chromatography), to provide qualitative and quantitative descriptions of metabolites in biological systems.…”
Section: Metabolomics In Ckdmentioning
confidence: 99%
“…Using this technology in a mouse model of AKI, authors concluded that the maladaptive repair in tubular cells is characterized by differences in production of lactate, which could possibly be the result of higher glycolytic activity and, as injury progresses, a concomitant reduction of the tricarboxylic acid (TCA) cycle metabolite consumption [ 34 ]. Over the past decades, metabolomics has added a promising number of new biomarkers through better pathophysiology knowledge, paving the way for insightful perspectives on the management of different kidney diseases [ 35 ]. However, the metabolome greatly varies with age, diet, drug consumption, lifestyle, and, in adults, with gender, making it difficult to compare studies in adults and in children and neonates.…”
Section: Fundamental Research Pushes Forward the Field Of Regenerativ...mentioning
confidence: 99%